Akar, posisi, dan aplikasi adat dalam hukum - Ahwan Fanani (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
Adat (custom) is a polemical topic in Islamic law. The development of Islamic law since the era of Prophet Muhammad has shown the important role of adat. Islamic law was formulated in accordance or in opposition to the custom of Arabs. However, classical Islamic legal theory (usul fiqh) does not consider it in legal argumentation. Its role is recognized in qawa‘id fiqhiyyah (principle of practical law) as one of five main principles. It is included in non-agreed legal argument. The paper is aimed to reveal the place of custom in Islamic law from the era of prophet to the contemporary era, especially in Islamic legal theory, in the principles of Islamic law, and in Islamic court according to manual book. This paper concludes that custom plays crucial role in elaborating Islamic law in practice. Custom has been acknowl- edged by Islamic scholars, especially by those of Hanafite and Malikite schools, as important part of Islamic law. However, they limites the role of custom in term of private law. The custom was never be discussed in term of rites and folklore, as it is popular now. The custom can still plays important role in Islamic private law or even in alternative dispute resolutions as far as traditional authority is needed and acknowledge by Islamic communities. Adat (custom) merupakan polemik dalam hukum Islam. Perkembangan hukum Islam sejak zaman Nabi Muhammad telah menunjukkan peran penting dari adat. Hukum Islam dirumuskan sesuai atau bertentangan dengan kebiasaan orang-orang Arab. Namun, teori hukum Islam klasik kita (usul fiqh) tidak mempertimbangkan dalam argumentasi hukum. Perannya diakui dalam qawa ‘id fiqhiyyah (prinsip hukum praktis) sebagai salah satu dari lima prinsip utama. Hal ini termasuk dalam argumen hokum yang tidak disepakati. Artikel ini bertujuan untuk mengungkapkan tempat adat dalam hukum Islam dari era Nabi ke era kontemporer, khususnya dalam teori hukum Islam, dalam prinsip-prinsip hukum Islam, dan di pengadilan Islam menurut buku manual. Tulisan ini menyimpulkan bahwa Adat memainkan peran penting dalam menguraikan praktek hukum Islam. Adat telah diakui oleh ulama Islam, terutama oleh orang-orang dari Mazhab Hanafi dan Maliki, sebagai bagian penting dari hukum Islam. Namun, mereka membatasi peran adat dalam hal hukum privat. Kebiasaan ini tidak pernah dibahas dalam hal ritual dan cerita rakyat, seperti yang populer sekarang. Kebiasaan masih bisa memainkan peran penting dalam hukum privat Islam atau bahkan dalam resolusi sengketa alternatif sejauh otoritas tradisional dibutuhkan dan diakui oleh masyarakat Islam.